Love and Quasars : An Astrophysicist Reconciles Faith and Science - Wallace, Paul, 1968- (Book collections on Project MUSE., 2019)
Like many Americans, Paul Wallace grew up as a church-going Christian. Also like many, he lost his faith when he started taking science classes in college. He just didn't see how the rigorous method demanded by science could coexist with the belief in things unseen required by Christianity. But, as a working astrophysicist, he started to wonder if he'd gotten something wrong. Slowly and deliberately, he investigated the claims of Christianity, while also acknowledging that science, too, has limits. Ultimately, he came back to Christianity. In Love and Quasars, Wallace shows how faith and science are pitted against one another, and he explains how the standard ways of reconciling them don't work. He then proposes a reasonable, thoughtful approach that will appeal to Christians and students of science alike. Readable and wise, Love and Quasars is an indispensable resource for people who wonder if faith and science can coexist.